A Deal with the Devil - Phillpotts, Eden, 1862-1960 (Salt Lake City, UT : Project Gutenberg, 2014)
"A Deal with the Devil" by Eden Phillpotts is a novel written in the late 19th century. The story revolves around Daniel Dolphin, a man celebrating his hundredth birthday, who makes a fateful pact with the Devil for an additional ten years of life, promising to grow younger instead of older. The narrative unfolds through the perspective of his granddaughter, Martha, as they grapple with the implications of this peculiar deal. The opening of the novel introduces Daniel Dolphin as a flawed but lively character reaching a remarkable age. On his birthday, he shares a humorous and unsettling dream featuring the Devil, who offers him a chance to extend his life by ten years in exchange for his soul. As Daniel contemplates this offer, Martha expresses her concern about the sinister consequences that may arise. Following the dream, Daniel discovers a formal agreement that suggests the pact is indeed real, provoking a mix of disbelief and horror for both him and Martha. This initial setup sets the stage for the unfolding chaos of their lives, leading to a blend of dark humor and poignant moments as they navigate the turmoil birthed from the Devil's bargain. (This is an automatically generated summary.)
Release date is 2014-10-30
Produced by Al Haines
Keywords: England -- Social life and customs -- 19th century -- Fiction; Grandparent and child -- Fiction; Devil -- Fiction; Rejuvenation -- Fiction